ANTITHROMBOTIC THERAPY IN PREVENTION OF CARDIOVASCULAR EVENTS (DEATH, ACUTE MYOCARDIAL INFARCTION, STROKE) IN PATIENTS WITH CHRONIC HEART FAILURE - N.D. Gerasimenko; M.S. Rasin (Проблеми екології та медицини)
Chronic heart failure is one of the main clinical challenges of modern medicine. The present paper discusses the features of antithrombotic therapy in prevention of cardiovascular events (death, acute myocardial infarction, stroke) in patients with chronic heart failure. It has been specified, which anticoagulants or antiplatelet agents have advantages taking into account the features of the functioning of organs and systems in patients with heart failure. Antithrombotic therapy is indicated for all patients with atrial fibrillation and heart failure. The feasibility of anticoagulant or antithrombotic therapy has not been proven in patients with sinus rhythm, since the risk of bleeding exceeds the antithrombotic effect in patients of this group. The results of controlled trials recommend anticoagulant therapy for patients with heart failure who are at high risk, particularly in atrial fibrillation, with previous thromboembolic episodes, a significant reduction in the left ventricular ejection fraction, intracardiac thrombosis and in patients with aneurysm. There is also no evidence to prescribe antithrombotic therapy for reducing the risk of stroke and thromboembolism in patients with heart failure and sinus rhythm. The choice of antithrombotic therapy should be guided by the CHA2DS2-VASc and HAS-BLAD indices.